Influence and practices of Gender-Based Violence in Dikwa Local Government Area of Borno State, Nigeria - Airaoje, Ojemeiri Karl; Aondover, Perpetua Ogechi; Uchendu, Chinelo Ebele; Obada, Aruaye Afeye; Akin-Odukoya, Omolara Oluwabusayo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
Gender-based violence (GBV) is a pervasive global issue that transcends cultural, social, and economic boundaries. Rooted in unequal power dynamics, it manifests in various forms, including physical, sexual, psychological, and economic abuse. In conflict-affected regions such as Borno State in Northeastern Nigeria, the prevalence and impact of GBV are particularly alarming. Decades of insurgency and terrorism by groups such as Boko Haram have not only caused widespread displacement but have also exacerbated existing gender inequalities, leading to increased vulnerability of women and girls to various forms of violence. This study examines the prevalence, factors, impacts, and strategies to combat Gender-Based Violence (GBV) in Dikwa Local Government Area of Borno State, Nigeria. Theoretically, the Ecological Model was used. Findings reveal that domestic violence (34.1%) is the most common form of GBV, followed by sexual violence (25.4%), human trafficking (24.2%), and harmful traditional practices (16.3%). Key drivers of GBV include forced marriages (54.2%), influenced by religious practices, cultural norms (26.1%), conflict (24.2%), and poverty (22.0%). The study highlights the multifaceted impacts of GBV, including educational disruption (30.7%), physical and mental health issues, family breakdowns, and increased vulnerabilities. Alarmingly, 59.5% of respondents reported a lack of access to essential support services. To address GBV, the study recommends the implementation community-wide educational programs to challenge harmful cultural practices, gender norms, and societal attitudes that perpetuate GBV.